2017
DOI: 10.1097/qai.0000000000001413
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Human Papillomavirus Vaccine Coverage Among Men Who Have Sex With Men—National HIV Behavioral Surveillance, United States, 2014

Abstract: Background Human papillomavirus (HPV) can cause oropharyngeal and anogenital cancers among men who have sex with men (MSM). In 2011, the Advisory Committee on Immunization Practices (ACIP) extended HPV vaccine recommendations to males through age 21 and MSM through age 26. Because of this distinction, vaccination for some MSM might rely on sexual behavior disclosure to health care providers. Receipt of ≥1 HPV vaccination among MSM aged 18–26 in National HIV Behavioral Surveillance (NHBS) was 4.9% in 2011. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 20 publications
3
28
1
Order By: Relevance
“…Socio-demographic variables implicated in previous research, such as ethnicity (e.g., [10]), education (e.g., [12]), and number of sexual partners (e.g., [11]) were not significantly associated with uptake in the present research. Age was also not a significant correlate of uptake, which may indicate that results from research concerning young MSM may be applicable to older men as well.…”
Section: Discussioncontrasting
confidence: 76%
“…Socio-demographic variables implicated in previous research, such as ethnicity (e.g., [10]), education (e.g., [12]), and number of sexual partners (e.g., [11]) were not significantly associated with uptake in the present research. Age was also not a significant correlate of uptake, which may indicate that results from research concerning young MSM may be applicable to older men as well.…”
Section: Discussioncontrasting
confidence: 76%
“…With the launch of a targeted HPV vaccination programme for MSM, the HPV vaccine uptake rate is at a level similar if not higher than what has been found in other studies. Two studies have shown that the HPV vaccine uptake rate was 21%17 and 17%29 among MSM aged 18–26 years in the USA. This highlights the fact that a targeted MSM programme is not sufficient to reach the critical vaccination threshold for MSM (at least 70%) 10 27.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Nevertheless, HPV vaccine uptake among young MSM is less than optimal, with fewer than 40% initiating the series (i.e., receiving ‡1 dose of the 3-dose series). [10][11][12][13][14] Although researchers have begun to identify promising strategies for promoting HPV vaccination among young MSM, [15][16][17] few evidence-based interventions are currently available.…”
Section: Introductionmentioning
confidence: 99%